2007
DOI: 10.1620/tjem.212.159
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Correlation of Helicobacter pylori Stool Antigen (HpSA) Test with the Severity of H. pylori-Related Gastritis

Abstract: The Helicobacter pylori (H. pylori) load in both stomach and stool and the resulting severity of gastritis are important criteria in validating the status of H. pylori infection. We aimed to assess the reliability of the H. pylori stool antigen (HpSA) test for the primary diagnosis of H. pylori infection by calculating the best cut-off value to obtain the highest sensitivity and specificity in dyspeptic patients. We also investigated the correlation of HpSA test with the severity of gastritis and H. pylori loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The remaining mild gastritis cases (69.2%) suffered from a single infection by either H. pylori or T. gondii. In consensus, it was reported that H. pylori antigen in stools was positive in 79/86 of antral or corpus gastritis cases, 19/21 of duodenitis cases, 2/2 of gastric ulcer cases, 8/8 of duodenal ulcer cases, 1/1 of gastric and duodenal ulcer cases and 17/21 of esophagitis cases [23] . It appears that our report is the first record of the effect of toxoplasmosis on gastritis severity in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining mild gastritis cases (69.2%) suffered from a single infection by either H. pylori or T. gondii. In consensus, it was reported that H. pylori antigen in stools was positive in 79/86 of antral or corpus gastritis cases, 19/21 of duodenitis cases, 2/2 of gastric ulcer cases, 8/8 of duodenal ulcer cases, 1/1 of gastric and duodenal ulcer cases and 17/21 of esophagitis cases [23] . It appears that our report is the first record of the effect of toxoplasmosis on gastritis severity in humans.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Turkey [45] investigated the quantitative correlation between the Premier Platinum HpSA and the severity of H. pylori ‐associated gastritis. After adjustment of the cut‐off level, the assay had a sensitivity and specificity of 92% and 100%, respectively.…”
Section: Noninvasive Methodsmentioning
confidence: 99%
“…All participants were required to attend the hospital for collection of blood and stool samples at 0, 4, 8, and 16 weeks (eight weeks after the completion of the intervention); the dates corresponded to study days 0, 28, 56, and 112, respectively. Stool samples were analyzed for H. pylori stool antigen (HpSA) using an HpSA-ELISA kit from Meridian Bioscience, Inc., as previously described [ 29 ]. Serum pepsinogens I and II (PGI and PGII) were measured in blood samples collected from volunteers at these same time points, and the PGI/PGII ratio was computed [ 30 , 31 ].…”
Section: Roles Of Sfn In Protection Against H Pylori mentioning
confidence: 99%